Perbandingan Kebijakan Portugal dan Hongaria Terhadap Pengungsi Timur Tengah 2015-2018 - Sunardi, Fieqry Ifvan; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Europe has been the continent in the spotlight since the middle of 2015, UNHCR report in 2015 showed 1,000,573 refugees from the Middle East fled to Europe because of the endless war and security uncertainty. Unfortunately the European Union is still divided over the refugee crisis. Although the European Union Commission has made a decision regarding the relocation scheme for refugees to be distributed fairly among EU countries, there are still some countries that reject the decision. As will be discussed in this study is the decision of the Portuguese government to accept refugees and the decision of the Hungarian government to reject refugees. The purpose of this study is to find out why Portugal and Hungary implemented different policies regarding the Middle East refugee problem. Specifically this research uses the theory of the national roles conception that see internal and external factors as forming the meaning of a country's national role. The study was conducted with qualitative method and descriptive research by using literature review in data collection. The results explain how different meanings of the national roles conception can influence the policies of the governments of Portugal and Hungary in the issue of accepting Middle Eastern refugees.